Maternal high-fat high-sucrose diet and gestational exercise modulate hepatic fat accumulation and liver mitochondrial respiratory capacity in mothers and male offspring - Stevanović-Silva, J (2021)
Background Maternal high-caloric nutrition and related gestational diabetes mellitus (GDM) are associated with a high-risk for developing metabolic complications later in life and in their offspring. In contrast, exercise is recognized as a non-pharmacological strategy against metabolic dysfunctions associated to lifestyle disorders. Therefore, we investigated whether gestational exercise delays the development of metabolic alterations in GDM mothers later in life, but also protects 6-week-old male offspring from adverse effects of maternal diet. Methods Female Sprague-Dawley rats were fed with either control (C) or high-fat high-sucrose (HFHS) diet to induce GDM and submitted to gestational exercise during the 3 weeks of pregnancy. Male offspring were sedentary and fed with C-diet. Results Sedentary HFHS-fed dams exhibited increased gestational body weight gain (p < 0.01) and glucose intolerance (p < 0.01), characteristic of GDM. Their offspring had normal glucose metabolism, but increased early-age body weight, which was reverted by gestational exercise. Gestational exercise also reduced offspring hepatic triglycerides accumulation (p < 0.05) and improved liver mitochondrial respiration capacity (p < 0.05), contributing to the recovery of liver bioenergetics compromised by maternal HFHS diet. Interestingly, liver mitochondrial respiration remained increased by gestational exercise in HFHS-fed dams despite prolonged HFHS consumption and exercise cessation. Conclusions Gestational exercise can result in liver mitochondrial adaptations in GDM animals, which can be preserved even after the exercise program cessation. Exposure to maternal GDM programs liver metabolic setting of male offspring, whereas gestational exercise appears as an important preventive tool against maternal diet-induced metabolic alterations.